2012
DOI: 10.1002/cncr.27739
|View full text |Cite
|
Sign up to set email alerts
|

Excision repair cross‐complementing gene‐1, ribonucleotide reductase subunit M1, ribonucleotide reductase subunit M2, and human equilibrative nucleoside transporter‐1 expression and prognostic value in biliary tract malignancy

Abstract: BACKGROUND: Tumor expression of excision cross-complementing gene-1 (ERCC1), human equilibrative nucleoside transporter 1 (hENT1), ribonucleotide reductase subunit M1 (RRM1), and ribonucleotide reductase subunit M2 (RRM2), is associated with the efficacy of platinum and gemcitabine chemotherapy. The authors of this report recently demonstrated that high ERCC1 and RRM2 expression levels are independent negative prognostic markers for survival in early stage pancreas cancer. The differential expression and progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…All personalized drugs were classified as targeted agents, and no cytotoxic agents were considered personalized. This finding may reflect the fact that the precise mechanism of action of cytotoxic agents and the biomarkers for them have only recently been explored (28,29). The hazard ratio for overall survival in the randomized trials was better with personalized treatment, although this did not reach statistical significance in multivariate analysis (P = 0.07).…”
Section: Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…All personalized drugs were classified as targeted agents, and no cytotoxic agents were considered personalized. This finding may reflect the fact that the precise mechanism of action of cytotoxic agents and the biomarkers for them have only recently been explored (28,29). The hazard ratio for overall survival in the randomized trials was better with personalized treatment, although this did not reach statistical significance in multivariate analysis (P = 0.07).…”
Section: Reviewmentioning
confidence: 98%
“…29). Agents that were tested with a personalized strategy were all considered to be targeted agents (Table 1).…”
Section: Characteristics Of Trialsmentioning
confidence: 99%
“…All pathologists were blinded to clinicopathologic variables and outcomes while assessing IHC results. The scoring system was modeled after one previously used at our institution designed to account for both staining intensity and percentage of cells staining (25, 26). No EGFR expression was defined as 0+ staining intensity in all tumor cells.…”
Section: Methodsmentioning
confidence: 99%
“…In BTCs, very little data exists on ERCC1. One study has suggested that low expression is a good overall prognostic indicator for PHCC and CBDAC,7 while another study suggested no predictive value 8. Recently, it was shown that ERCC1 was unable to predict response in patients undergoing platinum-based palliative chemotherapy 9.…”
Section: Introductionmentioning
confidence: 99%